Pengaruh Persepsi Risiko dan Promosi Terhadap Keputusan Pembelian pada Onlineshop Tokopedia: (Studi Pada Konsumen di Kabupaten Bogor) - Widarma Widarma; Muhammad Rusdi Ridjal (AKUNTANSI 45, 2024)
The research results show that: (1) The results of partial hypothesis testing prove that the risk perception variable influences the purchasing decisions of Tokopedia Onlineshop consumers in Bogor Regency. This is proven by the calculated t value of the risk perception variable of 8.206 > t table 1.984 with a significance of 0.000 < 0.05. (2). The results of partial hypothesis testing prove that promotional variables influence the purchasing decisions of Tokopedia Onlineshop consumers in Bogor Regency. This is proven by the calculated t value of the promotion variable of 4.086 > t table 1.984 with a significance of 0.000 < 0.05. (3) The results of simultaneous hypothesis testing prove that simultaneously the risk perception and promotion variables are proven to have an influence on the purchasing decisions of Tokopedia Onlineshop consumers in Bogor Regency. This is shown by the calculated F value of 257,690 > F table of 2,696 with a significance of 0.000 <0.05. (4) The variable that dominantly influences the purchasing decisions of Tokopedia online shop consumers in Bogor Regency is the risk perception variable with a regression coefficient value of 0.644. (5) The coefficient of determination test results obtained an adjusted R2 value of 0.838. This shows that the purchasing decisions of Tokopedia Onlineshop consumers in Bogor Regency are jointly influenced by perceptions of risk and promotion by 83.8%, while the remaining 16.2% of Tokopedia Onlineshop consumer purchasing decisions in Bogor Regency are influenced by other factors which in this study were not discussed.